Idiopathic Pulmonary Arteriovenous Malformation: A Case Report - Abdul Samad; Farah Naz; Nauman Ismat Butt; Zubair Ashraf; Muhammad Sohail Ajmal Ghoauri; Ayesha Zahid (Indian Journal of Respiratory Care)
Pulmonary arteriovenous malformation (PAVM) is a rare abnormal connection between a pulmonary vein and a pulmonary artery, resulting in blood bypassing the capillary bed and causing right-to-left shunting. We aim to report a case of idiopathic PAVM managed with coil embolization to highlight this rare disease. A 15-year-old girl presented with a 2-year history of progressively worsening shortness of breath on exertion and intermittent self-limiting hemoptysis. She had cyanosis with an oxygen saturation of 86% on room air. No telangiectasia was seen. Chest X-ray revealed nonhomogeneous opacifications, most marked in the right lower zone. High-resolution computed tomography (HRCT) chest demonstrated centrilobular nodules, some with a branching pattern in the anterior segment of the right upper lobe and apical segments of both the right upper and lower lobes; interlobar and intralobar septal thickening along with a prominent bronchovascular bundle in the right upper and lower lobes. CT pulmonary angiography revealed multiple dilated and enlarged serpiginous vessels in the right lung; in the arterial phase, simultaneous opacification of arteries and veins demonstrated a connection between the pulmonary artery and veins, consistent with the diffuse type of PAVM. A diagnosis of idiopathic diffuse PAVM was made, and three sessions of coil embolization were performed over a period of 1 year. By the 12-month follow-up, she was stable and asymptomatic. PAVM is a rare occurrence, and early screening with prompt management is required to improve prognosis. Our patient, who presented with shortness of breath and hemoptysis, was diagnosed with idiopathic PAVM. She refused surgery and was managed with coil embolization, which resulted in marked improvement. The differential diagnosis of shortness of breath includes respiratory, cardiac, and hematological diseases. A high index of clinical suspicion is required to timely diagnose PAVM to reduce complications and morbidity. PAVM is best managed by a multidisciplinary team encompassing an internist, pulmonologist, interventional radiologist, and cardiothoracic surgeon.